Does inclusion of glutamine in oral rehydration solutions improve recovery from mild to moderate diarrhoea in preweaned calves?. (17th September 2016) - Turner, Andrea; Rees, Gwen; Barrett, David C.; Reyher, Kristen K.
Abstract : Critically Appraised Topics (CATs) are a standardised, succinct summary of research evidence organised around a clinical question, and a form of evidence synthesis used in the practice of evidence‐based medicine (EBM) and evidence‐based veterinary medicine (EBVM). Access to CATs enables clinicians to incorporate evidence from the scientific literature into clinical practice and they have been used to teach EBVM at the University of Bristol's School of Veterinary Sciences since 2011. Veterinary Record is including CATs from Bristol university in its Clinical Decision Making section. The first of these, along with an explanation of how they can be used, was published in VR, January 30, 2016, vol 178, pp 118‐119.